An analysis of the factors affecting Irish citizens' willingness to invest in wind energy projects. (February 2023) - Sirr, Gordon; Power, Bernadette; Ryan, Geraldine; Eakins, John; O'Connor, Ellen; le Maitre, Julia
Abstract: Wind energy has a pivotal role to play in the transition to renewable energy. However, social opposition to developer-owned wind farms is a key barrier to its deployment. While research suggests that co-ownership arrangements between developers and communities could help to alleviate opposition, such arrangements are subject to market acceptance issues related to citizens' appetite for investing. This paper explores the issue of market acceptance of citizen investment opportunities in wind farms by examining citizens' willingness to invest in projects. Based on a survey of 2, 023 Irish citizens, we find that 56% of citizens would invest in a local project, 41% would invest in a portfolio of projects, and 29% would invest in a non-local project. Our empirical analysis reveals a number of socio-demographic, locational, community and attitudinal variables that affect both the decisions of citizens to invest in projects and the monetary amount that they are willing to invest. The findings of the paper provide insights into policy measures that could help to strengthen the market acceptance of citizen investment opportunities and will be useful for policymakers who are seeking to mobilise citizen investment with a view to enhancing the deployment of wind energy. Highlights: Market acceptance is evident in the case of local wind energy projects. Citizens are found to prefer local over non-local or portfolio investments. Financial investment experience is found to affect citizens' investment decisions. Income and wealth are found to affect the size of citizen investments. Policies may be needed to ensure shares are affordable.